Aprendizagem investigativa sobre a dengue empregando a educação STEAM e métodos ativos no ensino médio - Santos, Patrícia Alves dos (2020)
Currently, Teaching by Investigation is a teaching approach with a strategy for learning concepts, establishing cause and effect relationships, carrying out collaborative work that favors the development of the subjects' power of argument and a more authentic view than is doing science. In view of this finding, we bring as a central question of the research whether “Does the Active Learning method allow youth protagonism with a view to reducing the number of cases and preventing Dengue?”. The objective is to develop skills, such as critical thinking and problem solving capacity, preparing citizens for the challenges of the future. In this sense, the present research used alternative active methods, integrating fields of knowledge that form the teaching model STEAM, an acronym for the areas of Science, Technology, Engineering, Arts and Mathematics. Such a model is considered an integrated didactic proposal that allows the development of a methodology based on projects, bringing the proposal of collaborative learning using the theme Dengue. The methodological path consisted of a pre-test and, after the application of the investigative didactic sequence, a post-test to verify if there were advances in the learning process of the students collaborating in this research, which aims, in general, to evaluate the influence of the method of active learning in the students' cognitive process, as well as contributing to behavioral changes that have an impact on their personal lives and on the quality of life of the community. The results show that there was motivation of the student to participate in investigative practices and discussions on the theme, as well as these in their responses showed the increase of knowledge at the end of the Investigative Didactic Sequence (SDI) and, strengthened skills and competences when using the STEAM approach, so necessary for their intellectual and socio-emotional development in our society.